Determination of expandability clay from San José de Cúcuta metropolitan area, by adding different percentages of sewage sludge (2019)
This article shows the research carried out on clay from the San José de Cúcuta metropolitan area, Colombia, to which was added several percentages of a wastewater sludge, which is called as a technological nutrient. The objective of the study is to find out with what percentage of technological nutrient the capacity of expansion of the granules is maximized. The methodology that was followed consists of four phases; preparation of raw materials; pelletizing of raw materials in granules of 5 to 10 millimeters; application of heat treatment in a rotary kiln at the pilot plant level; and application of descriptive statistics for analysis of results. It was determined that the mixture with a 20% of technological nutrient, produces the highest volumetric expansion ratio, with 1.56 times its initial size, while, when adding 30% of the nutrient the same expansion occurs when adding an 10% nutrient, which is 1.07 times the initial size of the particle.